2010
DOI: 10.1136/adc.2010.186080
|View full text |Cite
|
Sign up to set email alerts
|

Sustained benefits of continuous subcutaneous insulin infusion

Abstract: The authors demonstrate that CSII is associated with significantly improved sustained glycaemic control, especially in preschool children with diabetes in motivated families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 5 publications
3
12
1
2
Order By: Relevance
“…[10][11][12][13][14] Moreover, the latter studies show a follow-up ranging from 1 to 5 years, [10][11][12][13][14] which is shorter than in the present work. Nevertheless, an observational study with a follow-up duration of 7 years reported, in an Italian cohort (and with the use of advanced pump features), only a stabilization of HbA1c level at the end of the follow-up.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…[10][11][12][13][14] Moreover, the latter studies show a follow-up ranging from 1 to 5 years, [10][11][12][13][14] which is shorter than in the present work. Nevertheless, an observational study with a follow-up duration of 7 years reported, in an Italian cohort (and with the use of advanced pump features), only a stabilization of HbA1c level at the end of the follow-up.…”
Section: Discussioncontrasting
confidence: 67%
“…[1][2][3][4][5] There is a substantial lack of data derived from randomized controlled trials of CSII versus MDI in children with a follow-up of >12 months, [6][7][8][9] but several observational studies have established that CSII use in children and adolescents is related to a significant and durable improvement of HbA1c levels. [10][11][12][13][14][15][16] Some variables at pump commencement-age, gender, HbA1c, glucose variability, diabetes duration, and frequency of daily self-blood glucose monitoring-are related to a subsequent better glycemic control, 2,3,17,18 but it is still controversial if starting CSII in patients with type 1 diabetes mellitus (T1DM) within 1 year of diagnosis results in better long-term glycemic control than starting it later. effectiveness and durability of insulin pump therapy in children and adolescents who have initiated CSII within 2 years after the diagnosis of T1DM.…”
mentioning
confidence: 99%
“…The mean percentage in each clinic on CSII therapy by study end was 7% [4][5][6][7][8][9][10] and the nurse to patient ratio ranged from 1 per 95 to 1 per 134. This is a similar level of staffing to other UK paediatric diabetes centres [12].…”
Section: Setting and Samplementioning
confidence: 99%
“…Outside a trial setting, only two observational studies have documented improved metabolic control for more than 12 months using CSII therapy [8,14], however both studies were uncontrolled.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated a clinically important improvement in hemoglobin A1c levels and a reduction in blood glucose variability as well as in hypoglycemic episodes in patients treated with CSII as compared with multiple daily injections (MDI). [1][2][3] Several studies that explored quality of life (QOL) suggested that patients undergoing CSII are significantly more satisfied with treatment than those receiving MDI. [4][5][6][7][8][9][10] These studies have used prospective comparisons in defined groups, typically from a single research center during the transition of patients to insulin pump therapy, thus representing potentially biased samples.…”
Section: Introductionmentioning
confidence: 99%